Interactions between HIV-1 Gag and Viral RNA Genome Enhance Virion Assembly - Dilley, Kari A. (J Virol, 2017)
Most HIV-1 virions contain two copies of full-length viral RNA, indicating that genome packaging is efficient and tightly regulated. However, the structural protein Gag is the only component required for the assembly of noninfectious viruslike particles, and the viral RNA is dispensable in this process. The mechanism that allows HIV-1 to achieve such high efficiency of genome packaging when a packageable viral RNA is not required for virus assembly is currently unknown. In this report, we examined the role of HIV-1 RNA in virus assembly and found that packageable HIV-1 RNA enhances particle production when Gag is expressed at levels similar to those in cells containing one provirus. However, such enhancement is diminished when Gag is overexpressed, suggesting that the effects of viral RNA can be replaced by increased Gag concentration in cells. We also showed that the specific interactions between Gag and viral RNA are required for the enhancement of particle production. Taken together, these studies are consistent with our previous hypothesis that specific dimeric viral RNA-Gag interactions are the nucleation event of infectious virion assembly, ensuring that one RNA dimer is packaged into each nascent virion. These studies shed light on the mechanism by which HIV-1 achieves efficient genome packaging during virus assembly. IMPORTANCE Retrovirus assembly is a well-choreographed event, during which many viral and cellular components come together to generate infectious virions. The viral RNA genome carries the genetic information to new host cells, providing instructions to generate new virions, and therefore is essential for virion infectivity. In this report, we show that the specific interaction of the viral RNA genome with the structural protein Gag facilitates virion assembly and particle production. These findings resolve the conundrum that HIV-1 RNA is selectively packaged into virions with high efficiency despite being dispensable for virion assembly. Understanding the mechanism used by HIV-1 to ensure genome packaging provides significant insights into viral assembly and replication.